Towards Finding Active Number of S-Boxes in Block Ciphers using Mixed Integer Linear Programming - Tiwari, Vikas; Jampala, Neelima; Naidu Tentu, Appala; Saxena, Ashutosh (Informatica, 2021)
Secure lightweight block ciphers have become an important aspect due to the fact that they are a popular choice for providing security in ubiquitous devices. Two of the most important attacks on block ciphers are differential cryptanalysis [1] and linear cryptanalysis [2]. Calculating the number of active S-boxes is one of the method to examine the security of block ciphers against differential attack. In this paper, we count the minimum number of active S-boxes for several rounds of the lightweight ciphers namely KLEIN, LED and AES. We utilized the method proposed in [9], where calculation of the minimum number of active S-boxes is formulated as a Mixed Integer Linear Programming (MILP) problem. The objective function is to minimize the number of active S-boxes, subject to the constraints imposed by the differential propagation of the cipher. The experimental results are presented in this paper and found to be encouraging.